Growth and Competitive Strategy in 3 Circles - Urbany, Joe E.; Davis, James H. (Open textbook library., 2012)
The 3-Circle model was developed over the past several years, initially in strategic planning for a university graduate program and in an executive MBA course designed to integrate the concepts of marketing and competitive strategy. Over the course of time, the 3-Circle model has been successfully used by hundreds of organizations throughout the world in establishing and growing their market positions. Many of the case examples in this book demonstrating applications of the 3-Circle model applications are from executives who have attended executive education training at the University of Notre Dame. The development of competitive strategy is difficult because there are a lot of moving parts, as well as hundreds of frameworks, that might potentially guide the effort. Executives appreciate how the 3-Circle model simplifies the integration of customer, firm, and competitor analysis to generate growth strategies. It also provides a common language and process for understanding and explaining competitive advantage and for identifying profitable growth strategy.